Number 12 (May 1982) - Southern Fishes Council (Southeastern Fishes Council Proceedings, 1982)
New Records, Distribution and Status of Ten Rare Fishes in the Tradewater and Lower Green River, Kentucky. By M.L. Warren and R.R. Cicerello, 8 pp.
Keywords: rare fishes; tradewater; lower green river; kentucky; fishes